2011
DOI: 10.1088/0031-9155/56/8/n01
|View full text |Cite
|
Sign up to set email alerts
|

Effects of formalin fixation on tissue optical polarization properties

Abstract: Formalin fixation is a preparation method widely used in handling tissue specimens, such as biopsies, specifically in optical studies such as microscopy. In this note, we examine how formalin fixation affects the polarization properties of porcine myocardium and liver as assessed by optical polarimetry. Spatial maps of linear retardance and depolarization were derived from four myocardial and four liver samples before and after formalin fixation. Overall, linear retardance and depolarization increased after fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 12 publications
1
36
1
Order By: Relevance
“…Small fixation effects were expected since immersion of the section in fixative may cause slight tissue displacement, deformation and shrinkage [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small fixation effects were expected since immersion of the section in fixative may cause slight tissue displacement, deformation and shrinkage [42].…”
Section: Discussionmentioning
confidence: 99%
“…Formalin fixation has been shown to affect optical polarization properties of myocardium and liver samples [42], and therefore fixation could affect our measurements in ocular tissues. To quantify the effects of formalin fixation on PLM-measured fiber orientation we used the following experiment: a fresh sheep eye was cryosectioned sagittally into 30 µm thick sections.…”
Section: Robustness To Tissue Fixationmentioning
confidence: 99%
“…Samples were moistened periodically with phosphate-buffered saline solution (0.02 M) to maintain freshness; this avoids potential complications associated with formalin fixation and other tissue handling or preparation methods. 18 Three previously reported low-birefringence (∼isotropic) tissues (liver, kidney cortex, and brain) and three highly birefringent (anisotropic) tissues (myocardium muscle, loin muscle, and tendon) were chosen. Liver was selected as an isotropic and highly absorbent tissue.…”
Section: Methodsmentioning
confidence: 99%
“…The tissue scattering coefficient (μ s ) is relatively lager than the values previously reported [75,76]. This increase may originate from formalin fixation since it has been reported that formalin fixation can result in increasing scattering coefficient due to the cross-linking of proteins creating a more highly scattering media [77,78]. …”
Section: Parameters For Tumor Detectionmentioning
confidence: 81%